A bibliometric analysis of light chain amyloidosis from 2005 to 2024: research trends and hot spots - Liu, Xiangdong; Wang, Junyan; Li, Yingmin; Shi, Weibo; Zhang, Xiaojing; Li, Shujin; Cong, Bin (Frontiers in Medicine, 2024)
Background Light chain (AL) amyloidosis stands as the most prevalent subtype of systemic amyloidosis, encompassing a group of rare diseases. Here, we evaluated the scientific landscape of AL amyloidosis to investigate research trends and identify hotspots within the field. Methods Relevant studies on AL amyloidosis published over the past two decades were retrieved from the Web of Science Core Collection. The publications between 2005 and 2024 were subjected to bibliometric analyses, leveraging tools including CiteSpace, VOSviewer, RStudio and MS Excel to analyse and visualize the annual publication trend, co-occurrence patterns, collaborative networks among countries, organizations, and authors. Burst keywords and references were also examined to obtain the research history, and emerging hotspots. Results The bibliometric analysis included 2,864 articles published between 2005 and 2024. The most productive journal is Amyloid-Journal of Protein Folding Disorders. The United States, along with several developed nations, emerges as a dominant force in international AL amyloidosis research. “AL amyloidosis” and “cardiac amyloidosis” were the primary hotspots over the past two decades, and “Biomarkers,” “Cardiac amyloidosis,” and “treatment” would be future trends. Conclusion This bibliometric analysis examined the research developments in AL amyloidosis over the past two decades using bibliometric software. Recent research in this field primarily focuses on two main areas: clinical diagnosis and treatment of AL amyloidosis, as well as cardiac amyloidosis. Emphasis is placed on understanding the mechanisms underlying immunoglobulin light chain aggregation and deposition to mitigate organ involvement.